Ejection fraction, B-lines, and global longitudinal strain evaluated with rest transthoracic echocardiography to assess prognosis in patients with chronic coronary syndromes - Lauro Cortigiani; Maria Francesca Orsino; Marco Favilli; Francesco Bovenzi (Exploration of Cardiology)
Aim: Transthoracic echocardiography (TTE) is the first-line imaging test for patients with chronic coronary syndrome (CCS) and the cornerstone of risk stratification is left ventricular (LV) ejection fraction (EF). Aim of the study was to investigate the value of TTE supplemented with strain echocardiography (STE) and lung ultrasound (LUS) to assess the risk of patients with CCS. Methods: In a prospective, single-center, observational study, from November 2020 to December 2022, 529 consecutive patients with CCS were recruited. All patients were evaluated at rest. A single vendor machine (GE Vivid E95) was used. EF with biplane Simpson’s method (abnormal cut-off < 50%), LV global longitudinal strain (GLS%, abnormal cut-off ≤ 16.2% by receiver-operating characteristics analysis) by STE, and B-line score (abnormal cut-off ≥ 2) by LUS (4-site simplified scan) were assessed. Integrated TTE score ranged from 0 (all 3 parameters normal) to 3 (all parameters abnormal). All patients were followed-up and a composite endpoint was considered, including all-cause death, acute coronary syndrome (ACS), and myocardial revascularization. Results: During a follow-up of 14.2 months ± 8.3 months, 72 events occurred: 10 deaths, 11 ACSs, and 51 myocardial revascularizations. In multivariable analysis, B lines [hazard ratio (HR) 1.76, 95% confidence Interval (CI) 1.05–2.97; P = 0.03], and GLS ≤ 16.2% (HR 2.0, 95% CI 1.17–3.45; P = 0.01) were independent predictors of events. EF < 50% was a significant predictor in univariate, but not in multivariable analysis. Event rate at 2 years increased from score 0 (8%), to score 1 (21%), 2 (23%), and 3 (40%), P < 0.0001. Conclusions: TTE with left ventricular ejection fraction (LVEF) can be usefully integrated with STE for GLS, and LUS for B-lines, for better prediction of outcome in CCS. The 3 parameters can be obtained in every echo lab with basic technology, no harm, no risk, and no stress.